Interfascial Plane Blocks: Chasing The Unseen - Raden Besthadi Sukmono (Majalah Anestesia & Critical Care, 2020)
Ultrasound has revolutionized anesthesia practice towards a better and safer technique. Regional anesthesia and pain medicine is one of the fields in anesthesiology that ultrasound has changed in so many ways. One of the main goals of regional anesthesia is to provide analgesia and immobility of certain parts of our body. In the early days of regional anesthesia, local anesthetics (LA) were injected blindly through a needle towards the biggest nerve responsible for innervating the surgical field. As technology advances, especially in image quality department, identification of deeper and smaller structures has become possible. We are now able to differentiate layers of neural structure (epineurium, perineurium, and endoneurium) with ultrasound image and manage to pinpoint the exact location for LA deposition. This translates as faster onset of blocks, enhancement of block quality, and safer blocks in terms of neurotoxicity and systemic toxicity. Regional anesthesia has long been employed as means of intraoperative and postoperative analgesia. Interfascial block works on a principle that by injecting local anesthetics in large volumes between two layers of fascia will create a potential space that bathe numerous neural targets residing in between these layers. This eventually block a certain area based on the extent of the space created. Multiple planar endpoints may exist for the same neural target due to the contiguous connection of fascial planes around the body. The knowledge of interconnecting potential space and multiple neural target opens the question that needed to be answered with studies and research about interfascial block. Are these minimally invasive blocks are as good as the real block? Will the clinical parameters and the future studies show that? We’ll look forward to see them in the near future.